Biodiversity arks in the Anthropocene - Honghu Meng; Xiaoyang Gao; Yigang Song; Guanlong Cao; Jie Li (Regional Sustainability, 2021)
The Anthropocene proposal suggested that the Earth may have entered a new geological epoch, in which human activity and climate change are influencing the environment at global scale. Arrival of the Anthropocene is bringing an unprecedented challenge to the biodiversity that is essential to humans, and enhancing many benefits of nature to human being. However, biodiversity loss is aggravating in the rhythm of inevitable change in the Anthropocene, and the adaptation of biodiversity to the anthropogenic disturbance seems unable to keep pace with the human activity and climate change. Therefore, re-examination of the assumptions and practices upon the current conservation endeavor are needed. We suggested that biodiversity conservation should be paid more attention to the response from biodiversity to the human activity and climate change in the Anthropocene. Thus, the concept of biodiversity arks in the Anthropocene is proposed, that is, biodiversity arks in the Anthropocene are the areas where vulnerable biodiversity is sheltered to alleviate human activity and buffered from climate change under the anthropogenic disturbance. The concept should be implemented for biodiversity conservation to fill gaps between our knowledge and build on successful conservation and sustainability in the Anthropocene. It will be certainly important to conservation policy instruction and management under climate change, especially the implementation of climate buffering zones preserving biodiversity in the face of warming climate.